Políticas de currículo organizado em ciclos : implicações entre conhecimento escolar e relações de poder na Escola Sarã (Cuiabá-MT) - Moura, Jucilene Oliveira de (2014)
This research broaches curriculum policy of organized in cycles, delimiting the study around of the curricular policy of the School Sarã of the city of Cuiabá-MT, in the period of 2006 to 2012. The aim is to comprehend the process of accomplishing of this policy of curricular organization in cycles of human formation, emphasizing how the resignification of this policy occurs in the different contexts and the relationship of power which establishes itself in the definition of the school knowledge. It is discussed the process of production of the political text and its unfolding in the context of the practice from the studies that comprehend the curricular policy as a non-linear cyclical process. It is discuss the curriculum in its historical, social and cultural dimensions. The theoretical-methodological foundation is the approach of the cycle of policies and the contemporary studies of the curriculum. The results of the analysis indicate that the curriculum policy of the School Sarã presents different theoretical-methodological perspectives. It is observed that there is the defense of a perspective of the curriculum favorably to the process of knowledge construction and human development and also the defense of a perspective of curriculum towards the interests of a productive world, coherent to the technical rationality, empowering the selection of contents and the culture considered legitimate by the tradition. The conflicts demarcate the arena of disputes circumscribed in the process of signification of the own curriculum, permeating the different contexts. From the analysis, it is observed a distancing of the curriculum based in the human formation to the approximation of an instrumental perspective of the curriculum, withdrawing the focus of the pedagogical process to the evaluation of the product, with emphasis in the results achieved. It is also emphasized that the politics of the School Sarã present hybrid conceptions of knowledge in their different contexts and they are constituted as a possibility of giving other signification and meanings to the curriculum.